Pengaruh penulangan geser pada balok beton non-pasir dengan agregat lempung bekah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The purpose (aim) of this research was to obtain the shear force could be retained by shear reinforcement of no fines, reinforced concrete beams. Ten no-fine beams (150 mm width, 200 mm height, 2000 mm long) with 8 D16 flexural reinforcement and 8 mm or diameter of shear reinforcement provided at various distance were padded. The walcer-cement ratio of the mix was 0.40, and the volumetric ratio between cement and aggregate was 1/4. The aggregate used was artificial light-weight made of expanded shale from Cilacap. The results showed that for beam with of 6 mm in diameter, the shear force that couia be retained by shear-reinforcement V5, couia be expressed by formula: Vs = 53,75 - 0,16.s, and for those with shear-reinforcement of 8 mm in diameter, the formula because: V, = 46,77 - 0,048.s. When s was the spacing of the shear reinforcement.